POLIGAMI DAN KRITERIA ADIL DALAM PERSPEKTIF ULAMA NUSANTARA - Muhammad Yusuf Siddik (STAI DI AL-HIKMAH, 2025)
This article examines polygamy and the criteria of justice from the perspective of Nusantara (Indonesian) scholars. The study is motivated by social realities showing that the practice of polygamy often leads to household conflicts, injustice, and even divorce, although it is not explicitly recognized as a direct legal ground for divorce in Indonesian positive law. This research aims to analyze the views of Nusantara scholars regarding the legal status of polygamy and the criteria of fairness required for its permissibility in Islam. This study employs a qualitative method through library research, using normative-juridical and conceptual approaches. Primary sources include the Qur’an, Hadith, Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law, and the works of prominent Nusantara scholars such as Shaykh Nawawi al-Bantani, Prof. Dr. Hamka, Prof. Dr. Quraish Shihab, H. Sulaiman Rasjid, Prof. Dr. Daud Rasyid, Prof. Dr. Asrorun Niam, and Dr. Muhammad Zaki bin Shaykh Abi Bakar. The data are analyzed descriptively and analytically to provide a comprehensive understanding of the concept and implications of polygamy in their perspectives. The findings reveal that Nusantara scholars generally agree that polygamy is permissible (mubah) under Islamic law, provided that the husband is capable of maintaining justice. Some scholars consider it recommended (sunnah) under certain circumstances. The criteria of justice primarily concern equality in financial support, housing, and the division of time (overnight stays), while emotional inclination or love is not included, as it lies beyond human control. Within the framework of national law, polygamy is recognized but subject to strict administrative requirements and judicial permission. Thus, polygamy in the perspective of Nusantara scholars is not an unrestricted practice but a conditional legal concession that requires fairness and responsibility to ensure the realization of justice, welfare, and harmony within the family.